Is the molecular clock ticking differently in bipolar disorder? Methylation analysis of the clock gene ARNTL. (31st October 2018) - Bengesser, Susanne A.; Reininghaus, Eva Z.; Lackner, Nina; Birner, Armin; Fellendorf, Frederike T.; Platzer, Martina; Kainzbauer, Nora; Tropper, Bernhard; Hörmanseder, Christa; Queissner, Robert; Kapfhammer, Hans-Peter; Wallner-Liebmann, Sandra J.; et al.
Abstract: Objectives: The clock gene ARNTL is associated with the transcription activation of monoamine oxidase A according to previous literature. Thus, we hypothesised that methylation of ARNTL may differ between bipolar disorder (BD) and controls. Methods: The methylation status of one CpG island covering the first exon of ARNTL (PS2) and one site in the 5′ region of ARNTL (cg05733463) were analysed in patients with BD ( n = 151) versus controls ( n = 66). Methylation analysis was performed by bisulphite-conversion of DNA from fasting blood with the EpiTect Bisulfite Kit, PCR and pyrosequencing. Analysis of covariances considering the covariates age, body mass index, sex, smoking, lithium and anticonvulsant intake were performed to test methylation differences between BD and controls. Results: Methylation at cg05733463 of ARNTL was significantly higher in BD than in controls ( F (1, 209) = 44.500, P < .001). In contrast, methylation was significantly lower in BD at PS2_POS1 compared to controls ( F (1, 128) = 5.787, P = .018) and by trend at PS2_POS2 ( F (1, 128) = 3.033, P = .084) and POS7 ( F (1, 34) = 3.425, P = .073). Conclusions : Methylation of ARNTL differed significantly between BD and controls. Thus, our study suggests that altered epigenetic regulation of ARNTL might provide a mechanistic basis for better understanding circadian rhythms and mood swings in BD.